Subarachnoid Sufentanil for Extracorporeal Shock Lithotripsy. Issue 1 (January 1997) - Eaton, Michael P.; Kristensen, E. A.
Abstract : Background and Objectives: Many different anesthetic techniques have been used for extracorporeal shock wave lithotripsy, each with its own benefits and disadvantages. A study was made to determine the efficacy and safety of subarachnoid sufentanil as an analgesic technique for lithotripsy. Methods: Eight consecutive patients from the University of Michigan Medical Center and twelve consecutive patients from the University of Vermont College of Medicine were retrospectively studied. The need for additional anesthesia, incidence of adverse effects, and discharge times were assessed. Results: Of the 20 patients, 18 were treated successfully with subarachnoid sufentanil. One patient had inadequate anesthesia. One procedure was postponed owing to intractable pruritus. Adverse effects occurred in four patients and were successfully treated. The mean discharge time was 132 minutes, which is comparable with those of other anesthetic methods. Conclusions: Subarachnoid sufentanil is a safe and effective technique for lithotripsy. A prospective study to compare it with other methods is justified.